2019
DOI: 10.1111/jcmm.14461
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor homologous factor 1 stimulates Leydig cell regeneration from stem cells in male rats

Abstract: Fibroblast growth factor homologous factor 1 (FHF1) is an intracellular protein that does not bind to cell surface fibroblast growth factor receptor. Here, we report that FHF1 is abundantly present in Leydig cells with up‐regulation during its development. Adult male Sprague Dawley rats were intraperitoneally injected with 75 mg/kg ethane dimethane sulphonate (EDS) to ablate Leydig cells to initiate their regeneration. Then, rats daily received intratesticular injection of FHF1 (0, 10 and 100 ng/testis) from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 73 publications
(165 reference statements)
0
13
0
Order By: Relevance
“…The primers for Cyp7b1 were: 5'-GAAGTCCTGCGTGACGAAAT-3' (forward); 5'-CCTCAGAACCTCAAGAATAGCG-3' (reverse); and the size of PCR product is 138 bp. For the internal standard, primers to ribosomal protein S16 (Rps16) were used, as described previously (28).…”
Section: Primer Selectionmentioning
confidence: 99%
“…The primers for Cyp7b1 were: 5'-GAAGTCCTGCGTGACGAAAT-3' (forward); 5'-CCTCAGAACCTCAAGAATAGCG-3' (reverse); and the size of PCR product is 138 bp. For the internal standard, primers to ribosomal protein S16 (Rps16) were used, as described previously (28).…”
Section: Primer Selectionmentioning
confidence: 99%
“…Rats were acclimated in the following conditions: 12 h dark/light cycle, 21-25°C, 55% relative humidity, and ad libitum access to water and food. At the time of experiment, the median weight of rats was 381 g (315 g~450 g) and the median age of rats was 67 d. After 7-d acclimation, each rat was given EDS (75 mg/kg body weight) via intraperitoneal injection [27]. Previous studies demonstrated that a single dose (75 mg/kg) of EDS killed all Leydig cells in the rat testis on the 7th day after EDS and Leydig cells were completely recovered 56 d later [3,9,28].…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…Total RNAs were purified from testes and STs using Trizol kit (Invitrogen, Carlsbad, CA) as previously described [27]. RNA concentration measurement, cDNA synthesis and qPCR with SYBR Green qPCR Kit (Roche, Basel, Switzerland) were conducted as previously described [13].…”
Section: Real-time Pcr (Qpcr)mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, their depletion in conditions such as ethane dimethanesulfonate is followed by the appearance of new, fully functional adult Leydig cells (254, 255), which are thought to arise from precursors stem cells (254). Very recently, it was shown in male rats that Fgf-homologous factor-1 (Fhf1 or Fgf12), an intracellular protein, is abundant in Leydig cells and that injection of Fhf1 resulted in Leydig cells regeneration from precursor stem cells in rats where Leydig cells were pharmacologically ablated (256).…”
Section: Testismentioning
confidence: 99%